Cryptic species diversity in marsupial frogs (Anura: Hemiphractidae: Gastrotheca) in the Andes of northern Peru - Duellman, William E.; Barley, Anthony J.; Venegas, Pablo J. (Zootaxa, 2014)
Molecular phylogenetic analysis revealed the existence of two undescribed species of the hemiphractid genus Gastrotheca in the Andes in northern Peru. Both species are similar morphologically to Gastrotheca dysprosita and G. monticola, but they differ from these species and from one another in subtleties of coloration and minor variances in size and proportions. Gastrotheca aguaruna sp. nov. (6˚10’50"S, 77˚37’01"W, 2480 m) is from humid forested areas in the northern part of the Cordillera Central, whereas G. aratia sp. nov. (6˚14’00"S, 78˚51’24"W, 2560 m ) is known from the northern part of the Cordillera Occidental.